(untitled) (Bangladesh Journal of Botany, 2018)
The essential oil of Salvia nemorosa L. was analyzed by GC-MS. The major constituents of the oil were E-caryophyllene (26.37%), phytol (16.92%), germacrene-D (15.34%), sabinene (12.86%), caryophyllene oxide (6.33%), bicyclogermacrene (4.71%) and n-tetradecane (2.45%). The total phenolic content and the antioxidant activity of methanolic extracts were determined with the Folin-Ciocalteau reagent and by the 2,2- diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay, respectively. The antimicrobial activity of the essential oil was individually evaluated against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli and Candida albicans using disc diffusion and serial dilution methods. The oil showed good antimicrobial activity against four medically important pathogens.